Impacts of drinking-age legislation on alcohol-impaired driving crimes among young people in Canada, 2009-13 - Callaghan, R.; Gatley, J.; Sanches, M.; Asbridge, M.; Stockwell, Tim (Wiley-Blackwell Publishing Ltd., 2016)
Background and aim: In Canada, the minimum legal drinking age (MLDA) is 18 years in Alberta, Manitoba and Québec and 19 in the rest of the country. Given that public health organizations have not only recommended increasing the MLDA to 19 years, but also have identified 21 years as ideal, the current study tested whether drivers slightly older than the MLDA had significant and abrupt increases in alcohol-impaired driving (AID) crimes, compared with their counterparts just younger than the MLDA. Design: Regression–discontinuity approach. Setting: Canada. Sample: AID criminal incidents by drivers aged 15–23 years (female, n = 10 706; male, n = 44 973). Measurements: Police-reported AID incidents from the Canadian 2009–13 Uniform Crime Reporting Survey. Findings: Significant gender × MLDA effects supported gender-specific models. Compared with males slightly younger than the MLDA, those just older had abrupt increases in AID incidents of 42.8% [95% confidence interval (CI) = 20.4–66.3%, P < 0.001], 28.1% (95% CI = 16.0–40.7%, P < 0.001) and 35.1% (95% CI = 22.4–48.4%, P < 0.001) in provinces with an MLDA of 18 years, 19 years and across the country, respectively. Among females, AID incidents increased by 39.9% (95% CI = 1.9–79.6%, P = 0.040) in provinces with an MLDA of 18 years, and by 19.4% (95% CI = 2.1–37.4%, P = 0.028) at the national level. Conclusion: Release from drinking-age restrictions appears to be associated with increases in alcohol-impaired driving offenses among young drivers in Canada, ranging from 28 to 43% among males and from 19 to 40% among females.